Ergonomics as a Relevant Factor in the Field of Nondestructive Testing (NDT) - Zdraveski, Filip; Caloska, Jasmina; Velkovski, Trajce; Djidrov, Marjan (SAR Journal, 2024)
NDT testing is a mandatory procedure in the manufacture of structures and equipment. It is a very useful procedure that embeds quality into the production process itself. It can be an automatic procedure, but for the most part it is a procedure carried out by an operator. The quality of the examination depends on the operator, and possible omissions. Ergonomics therefore plays an important role in the final result and is the subject of research in this paper. Ergonomics plays a significant role, especially in conditions where testing equipment is at a height, located in difficult-to-access spaces, confined spaces, or when using test equipment that requires engagement of muscular structure and the eyes.